The Interaction of Formal and Informal Contracts in the Decision of Cooperation of the Agents - TATIANA IWAI (2016)
Given the existent risk of opportunism in transactions, formal and informal contracts play a central role in the decision of cooperation of the agents. The study aimed to compare the effectiveness of formal and informal contracts in the decision of cooperation of the agent and also to investigate their joint effects of substitution or complement on the cooperation of the agents. For that, an experiment was performed to test in a laboratorial environment the behavior of agents under the pressure of both contracts. The results of the experiment showed that informal contracts are more effective to guarantee cooperation among agents. Furthermore, formal and informal contracts can be used as substitutes or complements according to the order in which they are applied. When formal contracts precede informal ones, there is an increase in cooperation levels among agents.